The mediating role of organizational learning capability and resilience in the error management culture-service innovation link and the contingent effect of error frequency - Akgun, Ali E.; Keskin, Halit; Aksoy, Zeynep; Fidan, Selahaddin Samil; Yigital, Suleyman (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
Error management culture (EMC) has received a significant interest in the service management literature. However, there remains a lack of studies investigating the underlying mechanisms (mediating variables) where EMC affects service innovation within the boundary condition of its moderating variables. This study investigates how EMC influences service innovation through organizational learning capability (OLC) and organizational resilience mechanisms. In addition, this study empirically examines the moderating role of error frequency on the relationship between EMC and OLC and organizational resilience. By investigating 300 service firms, this study empirically reveals that (a) EMC positively relates to OLC and organizational resilience; (b) OLC positively relates to organizational resilience; and (c) OLC plays a mediating role in the relationship between EMC and service innovation. This study also demonstrates that error frequency weakens the relationship between EMC and OLC in service firms.
Keywords: Social justice; principals; administration; error management culture; learning capability; organizational resilience; service innovation; error frequency; RESOURCE-BASED VIEW; DYNAMIC CAPABILITIES; QUALITY MANAGEMENT; FIRM; PERFORMANCE; ORIENTATION; ENGAGEMENT; CAPACITY; CRISIS; HOTELS; Business & Economics